Peningkatan Kemampuan Higher Order Thinking Skill Melalui Penggunaan Contextual Teaching and Learning - Alpi Zaidah; Alpiana Hidayatulloh; Mulia Rasyidi (LEMBAGA PENELITIAN DAN PENDIDIKAN (LPP) ARROSYIDIN, 2025)
The purpose of this study is to improve higher order thinking skills (HOTS) through the use of Contextual Teaching and Learning (CTL) in junior high school science subjects. Study this is study action classes (PTK) implemented at SMP Negeri 1 Pringgasela Class VIII Semester I of the year 2024/2025 lessons of 30 people. Technique data collection used is use instrument HOTS test choices double And sheet observation for measure implementation CTL learning . While the data is being analyzed with use technique descriptive qualitative. Results study this show that after implementing CTL, ability higher order thinking skills (HOTS) students experience significant improvement? in every cycle. On cycle 1 Improvement ability higher order thinking skills (HOTS) are marked with improvement percentage average value of results HOTS test for students namely with percentage average value of 16.67 % stage pre-action to 73.33% after action cycle 1 with criteria Enough Good And return increase after done action cycle 2 with percentage average value of 90.00% with criteria good. Usage Contextual Teaching and Learning (CTL) is capable increase ability students' higher order thinking skills (HOTS). Because involving learning in context real, encouraging experience active students , and involving they in think critical.